Role of the local structure in superconductivity of LaO0.5F0.5BiS2−xSex system. (6th March 2017) - Paris, E; Mizuguchi, Y; Hacisalihoglu, M Y; Hiroi, T; Joseph, B; Aquilanti, G; Miura, O; Mizokawa, T; Saini, N L
Abstract: We have studied the local structure of LaO0.5 F0.5 BiS2− x Se x by Bi L1 -edge extended x-ray absorption fine structure (EXAFS). We find a significant effect of Se substitution on the local atomic correlations with a gradual elongation of average in-plane Bi-S bondlength. The associated mean square relative displacement, measuring average local distortions in the BiS2 plane, hardly shows any change for small Se substitution, but decreases significantly for x ⩾ 0.6 . The Se substitution appears to suppress the local distortions within the BiS2 plane that may optimize in-plane orbital hybridization and hence the superconductivity. The results suggest that the local structure of the BiS2 -layer is one of the key ingredients to control the physical properties of the BiS2 -based dichalcogenides.